Asuhan Kebidanan Komprehensif pada Ny. S Umur 33 Tahun G2P1A0 di Wilayah Kerja UPTD Puskesmas Pabelan Kab Semarang - Widya Wahyu Utami; Rini Susanti (Universitas Ngudi Waluyo, 2024)
Midwives have an important role as implementers such as, midwives perform pregnancy obstetric care to family planning acceptors, midwives as managers such as, managing public health activities, especially about mothers and children and midwives as educators such as, midwives provide health education and counseling to clients, train and guide cadres. The benefits of midwifery care are to reduce maternal mortality (MMR) and infant mortality (IMR). Based on the description, The author is interested in doing midwifery care entitled “Continuty of Care (CoC) midwifery care in Ny.S at UPTD Puskesmas Pabelan ”. The method used is descriptive research method with the type of case study (Case Study). The study was conducted at UPTD Puskesmas Pabelan and patient homes from May to November 2024. The subjects in this study were pregnant women. S age 33 years old G2P1A0. The instrument used is SOAP method. Data collection techniques used are observation, interview, and documentation. Obtained results on the care of pregnancy assessment conducted by the authors of the Ny. “S